(untitled) (Tzintzun, Revista de Estudios Históricos, 2021)
In 1597, the Port of Campeche was assaulted by the English corsair William Parker. The raid faced the opposition of the villagers, who expelled the leader of the expedition and part of his crew, leaving as balance some sailors killed in combat, others captured by the dwellers, who referred them to the civil authorities to process them for piracy and three others ran with another fate when arrested by order of the Court of the Holy Office of the Inquisition of Mexico to be prosecuted for Lutheranism and piracy between 1598 and 1601. The purpose of this text is to review the way in which the Court of the Faith carried out the judgments against these mariners and the influence that the Anglo-Spanish relations of the end of the XVI century could have on the sentences handed down to these prisoners.